The application of emerging immunotherapy in the treatment of prostate cancer: progress, dilemma and promise - Che, Jizhong; Liu, Yuanyuan; Liu, Yangyang; Song, Jingheng; Cui, Hongguo; Feng, Dongdong; Tian, Aimin; Zhang, Zhengchao; Xu, Yankai (Frontiers in Immunology, 2025)
In recent years, there has been a growing trend towards the utilization of immunotherapy techniques for the treatment of cancer. Some malignancies have acquired significant progress with the use of cancer vaccines, immune checkpoint inhibitors, and adoptive cells therapy. Scholars are exploring the aforementioned methods as potential treatments for advanced prostate cancer (PCa) due to the absence of effective adjuvant therapy to improve the prognosis of metastatic castration-resistant prostate cancer (mCRPC). Immunotherapy strategies have yet to achieve significant advancements in the treatment of PCa, largely attributed to the inhibitory tumor microenvironment and low mutation load characteristic of this malignancy. Hence, researchers endeavor to address these challenges by optimizing the design and efficacy of immunotherapy approaches, as well as integrating them with other therapeutic modalities. To date, studies have also shown potential clinical benefits. This comprehensive review analyzed the utilization of immunotherapy techniques in the treatment of PCa, assessing their advantages and obstacles, with the aim of providing healthcare professionals and scholars with a comprehensive understanding of the progress in this field.